Analisis Perbandingan Kuat Tekan Beton Terhadap Penggunaan Pasir Alam Dan Pasir Pecah - Reni Nur Anggraini; Fadrizal Lubis; Widya Apriani (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2022)
The development of the construction industry in Indonesia is quite rapid, where almost all construction buildings use concrete as the main material. For certain areas or even at certain times where the natural conditions are not good (flood), it will be difficult to get sand. In this case, other alternatives are needed, not only from nature, for example from a stone crusher factory. In the Riau area there is a stone crusher factory, namely PT. Riau Mas Bersaudara where one of the products is crushed sand. The purpose of this study was to determine the ratio of the compressive strength of concrete resulting from the use of natural sand and crushed sand. In this study using the experimental method, namely the method by conducting experiments in the laboratory to get the results. The design concrete quality is K225 or equivalent to 18,675 MPa. Compressive strength testing based on SNI 1974:2011, the results of the study obtained that the average compressive strength at the age of 7 days of concrete with a mixture of natural sand was 17.625 MPa and concrete with a mixture of crushed sand was 13,841 MPa. From these results, it has been shown that the compressive strength of concrete using natural sand is higher than the compressive strength of concrete using crushed sand.